Treatment of Pauwels type III femoral neck fracture with medial femoral neck support screw: a biomechanical and clinical study - Zhichao Gao (Nature Portfolio, 2021)
Abstract A femoral neck fracture is currently one of the most common types of fracture in clinical practice. The incidence continues to increase due to traffic accidents, trauma, and osteoporosis. This research includes a biomechanical study and a clinical retrospective study. In the biomechanical studies, three groups’ effects (Control Group: 3CCS, DHS group, and study Group: 3CCS + mFNSS group) were compared by vertical compression tests, torsion tests, and fatigue tests. All the data were collected and analyzed. We subsequently performed a retrospective analysis of 131 patients with femoral neck fractures. The operative time, intraoperative blood loss, quality of postoperative fracture reduction, and follow-up observation of fracture healing, screw retreatment rates and fixation failure rates, as well as femoral head necrosis rates and hip function in two groups with 3CCS and 3CCS + mFNSS were compared. By the biomechanical study, we found that 3CCS + Mfnss group were biomechanically superior to 3CCS group and superior to the DHS group in terms of resistance to torsion. However, it was less effective than the DHS group in compressive strength and fatigue resistance. In terms of clinical application, 3CCS + mFNSS group was found to have lower screw retreatment rates and femoral head necrosis rates, and to have better fracture healing rates than group with 3CCS, indicating that medial support screws can effectively resist the vertical shear forces of fracture ends and promote the stability and healing of fracture ends, as well as to reduce the incidence of postoperative complications.